Tracing the Trajectory and Response of Islamic Law to Organ Transplantation According to the Scales of Shari'ah - Ramadhan, Agung Ilham; Mustofa, Imron (al-Rasῑkh: Jurnal Hukum Islam, 2025)
The medical field is gradually beginning to reveal its new breakthroughs related to the discovery of new treatment methods in the form of organ transplantation or the transfer of human organs to save other human organs, which is referred to as transplantation. The urgency of this practice is directed towards individuals who exhibit symptoms of organs detached from normal conditions. The aim of this research is to explore the Islamic legal response to transplantation practices that have not been specifically addressed in the Qur'an. Qualitative research is employed as a method, utilizing a comparative approach to the views of classical and modern scholars in conjunction with the fatwas of religious bodies. The findings of this study demonstrate that the Islamic legal response is very flexible in permitting transplantation practices, thereby making the medical world a bridge for the healing of humanity. This modern treatment method minimizes disparities in the medical field. This article can enrich the literature on organ transplantation by thoroughly analyzing the opinions of classical and contemporary scholars, thus necessitating the drafting of a new fatwa while considering the medical, social, and spiritual dynamics of the Islamic community.